IDENTIFIKASI KEANEKARAGAMAN DAN POLA PENYEBARAN MAKROALGA DI DAERAH PASANG SURUT PANTAI PIDAKAN KABUPATEN PACITAN SEBAGAI SUMBER BELAJAR BIOLOGI - Budi Setyawan, Ilham; Prihanta, Wahyu; Purwanti, Elly (University of Muhammadiyah Malang, 2015)
IDENTIFIKASI KEANEKARAGAMAN DAN POLA PENYEBARAN MAKROALGA DI DAERAH PASANG SURUT PANTAI PIDAKAN KABUPATEN PACITAN SEBAGAI SUMBER BELAJAR BIOLOGI Â Ilham Budi Setyawan1, Wahyu Prihanta1, dan Elly Purwanti1 1Program Studi Pendidikan Biologi, FKIP, Universitas Muhammadiyah Malang e-mail: marovisepuxanir@gmail.com Â Â ABSTRACT Â This research aimed to find out variance, ecology parameter,variance index,and dispersion pattern of macroalgae existed in intertidal pidakan beach sub-district Pacitan Residence.The results of research in the area of tidal beach Pidakan on 90 plots was found in 1925 with 17 individual macro algae species originating from the third division Rhodophyta, Chlorophyta and Phaeophyta.Variance index of (Hâ) was high richness category and value (E) was means community tend to flat. Index of Morisita (IM) mean dispersion of all Macroalgae was clumped. As a complement to the results of the study are used as a learning module macroalgae for SMA/MA. Keywords: identification, diversity, macroalgae, beach, Pacitan